Sertraline as a new potential anthelmintic against Haemonchus contortus: toxicity, efficacy, and biotransformation - Zajíčková, Markéta; Prchal, Lukáš; Navrátilová, Martina; Vodvárková, Nikola; Matoušková, Petra; Vokřál, Ivan; Nguyen, Linh Thuy; Skálová, Lenka (Veterinary research, 2021)
Haemonchus contortus is a parasitic nematode of ruminants which causes significant losses to many farmers worldwide. Since the drugs currently in use for the treatment of haemonchosis are losing their effectiveness due to the drug-resistance of this nematode, a new or repurposed drug is highly needed. As the antipsychotic drug sertraline (SRT) has been shown to be effective against the parasitic nematodes Trichuris muris, Ancylostoma caninum and Schistosoma mansoni, the aim of the present study was to evaluate the possible effect of SRT on H. contortus. The potential hepatotoxicity of SRT was tested in sheep, a common H. contortus host. In addition, the main metabolic pathways of SRT in H. contortus and the ovine liver were identified. While no effect of SRT on H. contortus egg hatching was observed, SRT was found to significantly decrease the viability of H. contortus adults in drug-sensitive and resistant strains, with its effect comparable to the commonly used anthelmintics levamisole and monepantel. Moreover, SRT in anthelmintically active concentrations showed no toxicity to the ovine liver. Biotransformation of SRT in H. contortus was weak, with most of the drug remaining unmetabolized. Production of the main metabolite hydroxy-SRT did not differ significantly between strains. Other minor metabolites such as SRT-O-glucoside, dihydroxy-SRT, and SRT-ketone were also identified in H. contorts adults. Compared to H. contortus, the ovine liver metabolized SRT more extensively, mainly via desmethylation and glucuronidation. In conclusion, the potency of SRT against H. contortus was proven, and it should be tested further toward possible repurposing.
Keywords: Haemonchus; Animals; ovce; Biotransformation; hemonchóza; zvířata; nemoci ovcí; Anthelmintics; Haemonchiasis; Sheep; biotransformace; Sheep Diseases; anthelmintika; Sertraline; sertralin